An investigation of the experiences of psychotherapists regarding Ubuntu in their psychotherapy practice: an interpretative phenomenological analysis - Qangule, Lumka Sybil (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
Psychotherapy is a Eurocentric concept and practice that has migrated to South Africa with technology, as part of the general transfer of knowledge (Mkhize, 2003). It has embedded Eurocentric principles that sometimes do not easily accommodate working with Africans. It has been practised by psychotherapists of African origin with clients of African origin, but is based upon Eurocentric ideas and guidelines for practice. Many African people consider their core values to be uBuntu, rooted in a principle 'umntu ngumntu ngabantu' (translated as 'a human being is a human being because of other human beings'). Some important features of uBuntu are interdependence, respect, spirituality and the primacy of communality as an approach to life. Some of the ways in which these impact on daily functioning are not foregrounded by adherence to Western principles. The use of only Eurocentric principles when working with clients of African origin may thus not lead to the desired outcomes in psychotherapy. However, these Eurocentric principles are recognised and enforced by the authoritative bodies in the field of psychology, such as the Health Professions Council of South Africa. A distinction will be made between the more inflexible ethical principles of psychology and the ideas of therapy frames. Therapy frames are not seen as being as rigid as ethical codes and they could be augmented, to be appropriate for the context, particularly in the commonly multicultural settings that are found here. Psychotherapists of African origin are torn between abiding by the ethical principles that they have been taught and practising in the way that they, together with their clients, have been socialised. Abiding by the principles as described in the codes is safe because it does not pose any threat of being sanctioned by the regulator of practice, but clients may be let down and there may be limited success with certain clients. This clash of ideas of ways of practice poses dissonance and many dilemmas among psychotherapists of African origin. Due to the nature of this study, Interpretative Phenomenological Analysis (IPA) was adopted as a suitable methodology, where eight practising amaXhosa psychotherapists were interviewed about their experiences of incorporating uBuntu in their psychotherapy practice. The raw data from initial interviews were analysed and the findings concluded that although psychotherapists were trained in Western ways of practice, they included some practices of uBuntu in their practice as well as upholding some Eurocentric principles that seemed to be helpful for their clientele. Subsequently a summary of the findings were discussed with participants in a focus group setting, where participants endorsed and expanded upon their original responses. With the above in mind, a psychotherapy model called uBuntu-Centred Psychotherapy was created, which reflects the principles and therapy frames that have been found to be useful in treating clients of African origin. This modality is more congruent with the worldviews and style of living of many South Africans, in the post-apartheid era. It embraces some Eurocentric principles that are relevant for Africans, while it is embedded in the phenomena and way of life reflected in uBuntu, a predominant mode of functioning for the group that was the focus of this study, the amaXhosa. The study ends by making recommendations for practice, as well as highlighting the need for further and more extensive research to contribute to the project of Africanising psychotherapy.
Keywords: Ubuntu (Philosophy); Psychotherapy -- Cross-cultural studies; Psychoanalysis and culture -- South Africa; Xhosa (African people) -- Psychology; Xhosa (African people) -- Mental health; Black people -- South Africa -- Psychology; Black people -- South Africa -- Mental health; Psychotherapists -- South Africa